TAX LITERACY AND SOCIAL ENVIRONMENT : INFLUENCING TAX AWARENESS IN SURABAYA'S GENERATION Z - Magdalena, Renna; Dendeng, Renaya Kezia; Mandy, Mandy; Prasetya, Daud Rexy Eka (LPPM STIE Muhammadiah Bandung, 2024)
This study evaluates the influence of tax literacy and social environment on tax awareness among Generation Z in Surabaya, Indonesia, using a sample of 200 individuals. A quantitative methodology was applied with data collected through face-to-face surveys using a questionnaire designed to measure tax literacy, perceptions of the social environment, and tax awareness. Analysis using linear regression shows that tax literacy has a significant and dominant influence on tax awareness, while the social environment also contributes positively but with a lower intensity. These results suggest the importance of integrating tax literacy and social environment support in public policy and education programs to enhance tax awareness in future generations. These findings are relevant for policymakers and educational institutions in designing effective strategies to strengthen tax compliance among the youth.